EX POST FACTO ANALYSIS OF VOCATIONAL TEACHERS' CREATIVITY DEFICITS USING PAVLOVA'S TAXONOMY IN YOGYAKARTA - Taufik Mus; Izzul Kiram Suardi; Eko Marpanaji (Universitas HKBP Nommensen, 2026)
The transformation of vocational education necessitates that educators possess adaptive digital skills. The objective of this study is to delineate the digital technology competency profile of vocational high school teachers in Yogyakarta City, employing Pavlova's (2009) taxonomy as a framework. Additionally, the study seeks to examine the correlation between this profile and the teachers' years of experience in the field. The present study employed a quantitative ex post facto design, and the sample comprised 284 teachers from 25 public and private schools. These teachers were selected through proportional random sampling. The data were collected using a validated questionnaire and analyzed using descriptive statistics and Spearman's rank correlation. The results of the mapping process indicated a clear distinction in the degree of mastery of competencies. Technological Awareness demonstrated the highest level of achievement in the